Compensation - Milkovich, George T. (McGraw-Hiill/Irwin, 2008)
As the market-leading text in its course area, COMPENSATION, 9th Edition by Milkovich and Newman offers current research material, in-depth discussion of topics, integration of Internet coverage, excellent pedagogy, and a truly engaging writing style. The 9th edition continues to examine the strategic choices in managing total compensation. The total compensation model introduced in chapter one serves as an integrating framework throughout the book. The authors discuss major compensation issues in the context of current theory, research, and real-business practices. Milkovich and Newman strive to differentiate beliefs and opinions from facts and scholarly research. They illustrate new developments in compensation practices as well as established approaches to compensation decisions.